Canada Goose foods: their significance to weight gain - Coleman, T S; Boag, D A (Wildfowl, 1987)
Major foods, taken by Canada Geese Branta canadensis while staging on the Nisutlin River delta in the Yukon Territory, were analysed for nutrient content. The most preferred of three food plants, rhizomes of Potomageton richardsonii, was lowest in fibre and protein content but highest in total non-structural carbohydrate (TNSC) content. The least preferred food, stems of Equisetum fluviatile, had the highest fibre content and lowest TNSC content. The third species, Equisetum palustre, was intermediate in preference and in content of the fibre. The value of the two species Equisetum to grazing geese was investigated by allowing one group of geese to graze only on stands of one species, and a second on stands of the other. Based on weight gain over 14 days, the value to geese of grazing on E. palustre was significantly greater than that of grazing on E. fluviatile.